Chairside finishing and polishing of modern dental ceramics: material-specific variations in surface roughness - Alrabiah, Mohammed; Binrayes, Abdulaziz; Alsayed, Hussain D.; Althumairy, Riyadh I.; Habib, Syed Rashid (Frontiers in Materials, 2026)
AimThis study examines the effects of chairside finishing and polishing on the surface roughness (SR) of zirconia (ZR), lithium disilicate (LD), and hybrid ceramics (HC) to identify material-specific variations and determine optimal clinical protocols for smooth, durable, and esthetic ceramic surfaces.MethodologyThree modern dental ceramics Zr (IPS e. max® ZirCAD), LD (IPS e. max® CAD), and HC (Vita Enamic®) were used to create 135 disc-shaped specimens. Each specimen (10 mm diameter×2 mm) was either glazed or finished polished following the protocols set for study. A Profilometer evaluated SR of the two surfaces in micrometers (μm), while the surface topography was examined using scanning-electron-microscope (SEM). Using SPSS, ANOVA and post hoc multi-comparison tests were used for statistical analysis.ResultsOne-way ANOVA revealed significant differences among groups (p < 0.05). For Zr, the glazed specimens exhibited the highest SR (p = 0.000), while OptraFine® and Diasynt® produced smoother surfaces with no significant difference between them (p = 0.226). In the LD group, Diasynt® showed significantly higher roughness compared with both OptraFine® and glazed specimens (p = 0.000), whereas OptraFine® and glazed groups did not differ significantly (p = 0.060). For HC, Diasynt® produced the highest roughness, followed by glazing, with OptraFine® yielding the smoothest surfaces. Overall, OptraFine® consistently yielded the lowest surface roughness across all materials, with LD exhibiting the smoothest surfaces (0.119 ± 0.031 µm).ConclusionSR of CAD/CAM ceramics was influenced by both material type and finishing method. OptraFine® consistently produced the smoothest surfaces. LD was the smoothest material, and ZR benefited more from polishing than glazing. Material-specific finishing is essential for optimal smoothness, esthetics, and durability.